2016
DOI: 10.1039/c5cy01521a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alkali metals on Pd/TiO2catalysts for catalytic oxidation of formaldehyde at room temperature

Abstract: We previously observed that sodium (Na) addition had a dramatic promotion effect on Pd/TiO 2 catalysts for formaldehyde (HCHO) oxidation. In this study, a series of alkali metal (Li, Na, K, Cs) doped Pd/TiO 2 catalysts were prepared and tested for ambient temperature HCHO oxidation. The results showed that the doped alkali metals have a common promotion effect on the performance of the Pd/TiO 2 catalysts for HCHO oxidation under ambient temperature, which followed the order K > Cs > Na > Li. X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(53 citation statements)
references
References 59 publications
1
51
1
Order By: Relevance
“…8 In recent years, complete oxidation of HCHO over heterogeneous catalysts has been considered to be the most promising strategy for indoor HCHO removal due to its properties of high efficiency and lack of pollution. Highly effective catalysts have been prepared to reduce HCHO, such as transition metal oxides [9][10][11] and supported noble metals (Pt, [12][13][14][15] Au, 16 and Pd 17 ). Generally, transition metal oxides can achieve complete oxidation of HCHO at very high temperatures (>100 C).…”
Section: Introductionmentioning
confidence: 99%
“…8 In recent years, complete oxidation of HCHO over heterogeneous catalysts has been considered to be the most promising strategy for indoor HCHO removal due to its properties of high efficiency and lack of pollution. Highly effective catalysts have been prepared to reduce HCHO, such as transition metal oxides [9][10][11] and supported noble metals (Pt, [12][13][14][15] Au, 16 and Pd 17 ). Generally, transition metal oxides can achieve complete oxidation of HCHO at very high temperatures (>100 C).…”
Section: Introductionmentioning
confidence: 99%
“…OCAL [40] believed that the peak around 460.2 eV was ascribed to TiO x /Ti. In our study, Pd and Pt possessed higher electronegativity (Pd-2.20, Pt-2.28) than Ti (1.62), which resulted in the electron transfer from Ti to Pd and Pt [41][42][43]. So the proportion of high-valence TiO x increased and the binding energy of TiO x /Ti peak for all the catalysts shifted to a higher position (by 0.6-0.8 eV (26.18).…”
Section: Xps Evaluatementioning
confidence: 81%
“…It is widely accepted that highly dispersed noble metal catalysts exhibited much superior O 2 activation ability, not just because of their abundant active sites, but also because highly dispersed noble metal particles with low‐coordination number possessed much superb O 2 activation ability . Therefore, supported noble metal catalysts with higher noble metal dispersion could exhibit better O 2 activation ability and similar phenomenon was also observed in literatures . And in fact, all Na promoted 1Pd/SBA‐15 catalysts with higher Pd dispersion exhibited better O 2 activation ability and possessed much more abundant chemisorbed oxygen species compared to 1Pd/SBA‐15, consequently leading to superb HCHO oxidation activity.…”
Section: Resultsmentioning
confidence: 99%
“…reported that alkali metal ions (such as Li + , Na + , and K + ) could stabilize an atomically dispersed Pt species in the form of Pt−O(OH) x ‐Na, resulting in its much better HCHO oxidation activity compared with Pt/TiO 2 . Analogously, the promotion role of alkali metal ions was also observed on the Pd/TiO 2 , Ag/Co 3 O 4 , and Pt/MnO 2 catalysts for HCHO catalytic oxidation . Nevertheless, researches mainly focused on the reducible oxides (such as TiO 2 , Co 3 O 4 , and MnO 2 ).…”
Section: Introductionmentioning
confidence: 99%